Strategi Pedagang Tradisional Pakaian Fashion Muslim dalam Menghadapi Transformasi Digital Bisnis - Pertiwi, Dwi Indah; Nurbaiti, Nurbaiti; Dharma, Budi (Jayapangus Press, 2024)
This study aims to analyze and provide alternative strategies for Muslim fashion clothing traders in the Aek Kanopan Inpres Market who are affected by e-commerce. This research uses qualitative methods to explore the strategies used by traders in facing digital transformation. The object of this research is the Aek Kanopan Inpres Market, with a sample of clothing traders selected using the purposive sampling method. Data was collected through observation, interviews, and documentation, then analyzed using three steps: data reduction, data presentation, and conclusion drawn. The results of the study show that merchants apply three main strategies in dealing with e-commerce: focus strategy, differentiation strategy, and low-cost advantage strategy. In the face of increasingly fierce e-commerce competition, traditional Muslim fashion clothing traders in the Aek Kanopan presidential market are implementing various practices to maintain the quality of their products and services. They prioritize product quality by choosing the best materials and following the latest trends in the clothing industry. In addition, they emphasize personalized and friendly service to each customer by holding special promotions and loyalty programs. A focus strategy involves prioritizing the service of loyal customers and maintaining a good relationship with them. The differentiation strategy emphasizes the importance of maintaining product quality and uniqueness to meet customer expectations and compete with e-commerce. The low-cost advantage strategy is implemented by maintaining competitive prices through direct purchases from wholesalers and the use of social media for promotion, which helps reduce marketing costs. Overall, although currently traders at Inpres Aek Kanopan Market operate traditionally, adopting these strategies can help improve competitiveness, attract more customers, and manage business more efficiently and effectively.